Influence of the Fermented Feed and Vaccination and Their Interaction on Parameters of Large White/Norwegian Landrace Piglets - Laurynas Vadopalas; Sarunas Badaras; Modestas Ruzauskas; Vita Lele; Vytaute Starkute; Paulina Zavistanaviciute; Egle Zokaityte; Vadims Bartkevics; Dovile Klupsaite; Erika Mozuriene; Agila Dauksiene; Sonata Sidlauskiene; et al. (Animals, 2020)
The aim of this study was to evaluate the influence of fermented with a newly isolated lactic acid bacteria (LAB) strains combination (Lactobacillus plantarum LUHS122, Lactobacillus casei LUHS210, Lactobacillus farraginis LUHS206, Pediococcus acidilactici LUHS29, Lactobacillus plantarum LUHS135 and Lactobacillus uvarum LUHS245) feed on non-vaccinated (NV) and vaccinated with Circovac porcine circovirus type 2 vaccine (QI09AA07, CEVA-PHYLAXIA Co. Ltd. Szállás u. 5. 1107 Budapest, Hungary) piglets’ blood parameters, gut microbial composition, growth performance and ammonia emission. The 36-day experiment was conducted using 25-day-old Large White/Norwegian Landrace (LW/NL) piglets, which were randomly divided into four groups with 100 piglets each: SnonV—non-vaccinated piglets fed with control group compound feed; SV—vaccinated piglets fed with control group compound feed; RFnonV—non-vaccinated piglets fed with fermented compound feed; RFV—vaccinated piglets fed with fermented compound feed. Samples from 10 animals per group were collected at the beginning and end of the experiment. Metagenomic analysis showed that fermentation had a positive impact on the Lactobacillus prevalence during the post-weaning period of pigs, and vaccination had no negative impact on microbial communities. Although a higher amount of Lactobacillus was detected in vaccinated, compared with non-vaccinated groups. At the end of experiment, there was a significantly higher LAB count in the faeces of both vaccinated compared to non-vaccinated groups (26.6% for SV and 17.2% for RFV), with the highest LAB count in the SV group. At the end of experiment, the SV faeces also had the highest total bacteria count (TBC). The RFV group had a 13.2% increase in total enterobacteria count (TEC) at the end of experiment, and the SV group showed a 31.2% higher yeast/mould (Y/M) count. There were no significant differences in the average daily gain (ADG) among the groups; however, there were significant differences in the feed conversion ratios (FCR) between several groups: SV vs. SnonV (11.5% lower in the SV group), RFV vs. RFnonV (10.2% lower in the RFnonV group) and SV vs. RFV (21.6% lower in the SV group). Furthermore, there was a significant, very strong positive correlation between FCR and TEC in piglets’ faeces (R = 0.919, p = 0.041). The lowest ammonia emission was in RFV group section (58.2, 23.8, and 47.33% lower compared with the SnonV, SV and RFnonV groups, respectively). Notably, there was lower ammonia emission in vaccinated groups (45.2% lower in SV vs. SnonV and 47.33% lower in RFV vs. RFnonV). There was also a significant, very strong positive correlation between ammonia emission and Y/M count in piglets’ faeces at the end of the experiment (R = 0.974; p = 0.013). Vaccination as a separate factor did not significantly influence piglets’ blood parameters. Overall, by changing from an extruded soya to cheaper rapeseed meal and applying the fermentation model with the selected LAB combination, it is possible to feed piglets without any undesirable changes in health and growth performance in a more sustainable manner. However, to evaluate the influence of vaccination and its interaction with other parameters (feed, piglets’ age, breed, etc.) on piglets’ parameters, additional studies should be performed and methods should be standardised to ensure the results may be compared.